Immunogenicity and safety of a 2-dose hepatitis B vaccine, HBsAg/CpG 1018, in persons with diabetes mellitus aged 60–70 years. Issue 39 (16th September 2019) - Hyer, Randall N.; Janssen, Robert S.
Graphical abstract: Highlights: HBsAg/CpG 1018 is a 2-dose hepatitis B vaccine. Adults with T2DM are at greater risk of contracting HBV than the general population. HBV vaccination is important in individuals with T2DM 60 years or older. HBsAg/CpG 1018 provides higher SPRs against HBV than 3-dose HBsAg/alum. Abstract: Background: Hepatitis B virus (HBV) remains a major public health issue, although it is a vaccine-preventable disease. Adults with diabetes are at greater risk of contracting HBV than the general population. Commonly used 3-dose HBV vaccines have reduced immunogenicity in older individuals and in those with diabetes mellitus. Methods: In this post hoc analysis of a phase 3 clinical trial, participants with type 2 diabetes mellitus aged 60–70 years received either 2-dose HBsAg/CpG 1018 (HEPLISAV-B®, n = 327) at 0 and 4 weeks and placebo at 24 weeks or 3-dose HBsAg/alum (Engerix-B®, n = 153) at 0, 4, and 24 weeks. Immunogenicity, including seroprotection rate (SPR) at week 28, and safety were assessed by subgroup (sex, body mass index, and smoking status). SPR was defined as antibody against hepatitis B surface antigen serum concentration ≥10 mIU/mL. Results: The SPR at week 28 was significantly higher with HBsAg/CpG 1018 (85.8% [235/274]) than with HBsAg/alum (58.5% [76/130]) in the per-protocol analysis, for an overall difference of 27.3% (95% CI, 18.0–36.8). SPRs with HBsAg/CpG 1018 were consistently markedly higher compared with HBsAg/alum, regardless of sex, body mass index, or smoking status. Adverse events and deaths were comparable between groups. Conclusions: Two-dose HBsAg/CpG 1018 provides a higher level of seroprotection against HBV than does a 3-dose vaccine (HBsAg/alum) with a similar safety profile in patients aged 60–70 years with type 2 diabetes mellitus. Study identifier: NCT02117934.